EORTC topics in neurooncology: the long path from a focus on neurological complications of cancer towards molecularly defined trials and therapies in neurooncology - Wick, Wolfgang (European journal of cancer. EJC Supplements, 2012)
Over the past decade a series of trials of the EORTC Brain Tumor Group (BTG) has substantially influenced and shaped the standard-of-care of primary brain tumors. All these trials were coupled with biological research that has allowed for better understanding of the biology of these tumors. In glioblastoma, EORTC trial 26981/22981 conducted jointly with the National Cancer Institute of Canada Clinical Trials Group showed superiority of concomitant radiochemotherapy with temozolomide over radiotherapy alone. It also identified the first predictive marker for benefit from alkylating agent chemotherapy in glioblastoma, the methylation of the O6-methyl-guanyl-methly-transferase (MGMT) gene promoter. In another large randomized trial, EORTC 26951, adjuvant chemotherapy in anaplastic oligodendroglial tumors was investigated. Despite an improvement in progression-free survival this did not translate into a survival benefit. The third example of a landmark trial is the EORTC 22845 trial. This trial led by the EORTC Radiation Oncology Group forms the basis for an expectative approach to patients with low-grade glioma, as early radiotherapy indeed prolongs time to tumor progression but with no benefit in overall survival. This trial is the key reference in deciding at what time in their disease adult patients with low-grade glioma should be irradiated. Future initiatives will continue to focus on the conduct of controlled trials, rational academic drug development as well as systematic evaluation of tumor tissue including biomarker development for personalized therapy. Important lessons learned in neurooncology are to dare to ask real questions rather than merely rapidly testing new compounds, and the value of well designed trials, including the presence of controls, central pathology review, strict radiology protocols and biobanking. Structurally, the EORTC BTG has evolved into a multidisciplinary group with strong transatlantic alliances. It has contributed to the maturation of neurooncology within the oncological sciences.